The Development of Nonsymbolic Probability Judgments in Children. Issue 3 (9th February 2019) - O'Grady, Shaun; Xu, Fei
Abstract : Two experiments were designed to investigate the developmental trajectory of children's probability approximation abilities. In Experiment 1, results revealed 6‐ and 7‐year‐old children's ( N  = 48) probability judgments improve with age and become more accurate as the distance between two ratios increases. Experiment 2 replicated these findings with 7‐ to 12‐year‐old children ( N  = 130) while also accounting for the effect of the size and the perceived numerosity of target objects. Older children's performance suggested the correct use of proportions for estimating probability; but in some cases, children relied on heuristic shortcuts. These results suggest that children's nonsymbolic probability judgments show a clear distance effect and that the acuity of probability estimations increases with age.